BLOUNT DISEASE EVALUATION OF THE OPERATIVE TREATMENT WITHIN 2006-2014 IN DR. SOETOMO GENERAL HOSPITAL SURABAYA - Komang Agung Irianto Suryaningrat; I. G. Ng. Dodo M. Ranuh (Universitas Airlangga, 2017)
Background: Blount disease is a growth disturbance of the medial side of the proximal physeal of the tibia, epiphyseal and metaphyseal. Clinically this disease marked by varus angulation and internal rotation of the tibia on the metaphyseal area below knee.Method: This paper evaluating 2 cases of blount disease treated surgically in Soetomo general hospital within 2006 – 2014. The evaluation based on MDA (meta-diaphyseal angle) pre and post operatively.Result: Showed significant and satisfactory to patients and parents who have carried out the operation. A reduction in the angle of MDA, in first patients the MDA angle before surgery was 18 degrees on the right 40 degrees on the left, after surgery MDA was 24 degrees on the right, 10 degrees on the left. The second patient MDA before surgery was 32 degrees on the right and 33 degrees on the left, after the surgery MDA was 12 degrees on the left side, for the right side hasn’t operated yet.Discussion and Conclusion: There is hope for correction on severe form of blount disease. Correction by performing a proximal tibia osteotomy on the affected bone.